A Cross-Sectional Assessment of Urinary Tract Infections Among Geriatric Patients: Prevalence, Medication Regimen Complexity, and Factors Associated With Treatment Outcomes - Akhtar, Ali; Ahmad Hassali, Mohamed Azmi; Zainal, Hadzliana; Ali, Irfhan; Khan, Amer Hayat (Frontiers in Public Health, 2021)
Background Urinary tract infections are the second most prevalent infection among the elderly population. Hence, the objectives of current study were to evaluate the prevalence of urinary tract infections among older adults, medication regimen complexity, and factors associated with treatment outcomes of elderly patients infected with urinary tract infections. Methods A retrospective cross-sectional study was conducted at Department of Urology, Hospital Pulau Pinang, Malaysia. Patients ≥ 65 years of age were included in present study with confirmed diagnosis of urinary tract infections from 2014 to 2018 (5 years). Results A total of 460 patients met the inclusion criteria and were included in the present study. Cystitis (37.6%) was the most prevalent urinary tract infection among the study population followed by asymptomatic bacteriuria (31.9%), pyelonephritis (13.9%), urosepsis (10.2%), and prostatitis (6.4%). Unasyn (ampicillin and sulbactam) was used to treat urinary tract infections followed by Bactrim (trimethoprim/sulfamethoxazole), and ciprofloxacin. Factors associated with treatment outcomes of urinary tract infections were gender (OR = 1.628; p = 0.018), polypharmacy (OR = 0.647; p = 0.033) and presence of other comorbidities (OR = 2.004; p = 0.002) among the study population. Conclusion Cystitis is the most common urinary tract infection observed in older adults. Gender, burden of polypharmacy, and presence of comorbidities are the factors that directly affect the treatment outcomes of urinary tract infections among the study population.